1999
DOI: 10.1097/00000374-199907000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Immune Changes in Alcohol-Dependent Patients Without Medical Disorders

Abstract: The findings suggest that although males with chronic alcohol dependence have compromised phagocytic function, chronic alcohol-dependent subjects who are free of medical disorders do not have substantial abnormalities in many immune system functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
3
14
2
Order By: Relevance
“…Schleifer and colleagues (1999), however, did not find such differences in alcohol-dependant adults without medical disorders compared to non-abusing controls. Follow-on work by Schleifer and colleagues (2002), which included alcohol-dependent adults with minor health abnormalities, also found no differences in CD8+ and other immune measures.…”
Section: Discussioncontrasting
confidence: 64%
“…Schleifer and colleagues (1999), however, did not find such differences in alcohol-dependant adults without medical disorders compared to non-abusing controls. Follow-on work by Schleifer and colleagues (2002), which included alcohol-dependent adults with minor health abnormalities, also found no differences in CD8+ and other immune measures.…”
Section: Discussioncontrasting
confidence: 64%
“…7,8 Alcohol is also known, however, to affect patients' immune system, and patients who have developed liver disease have different immunological behaviour than patients who misuse alcohol but have normal liver function. 19 There may therefore be an immunological mechanism underpinning excess alcohol consumption in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…As with other consequences of alcohol exposure (Hoek et al, 2005; Bravo et al, 2012), there appear to be gender differences in alcohol’s effects on phagocytic function. For example, Schleifer et al, (1999) found decreased phagocytosis in alcohol-dependent males, but not in females. There is some evidence that alcohol’s effects also differ among the phagocytic cells (Schleifer et al, 1999).…”
Section: Psychoneuroimmunological Analysis Of Substance Use Disordersmentioning
confidence: 98%
“…For example, Schleifer et al, (1999) found decreased phagocytosis in alcohol-dependent males, but not in females. There is some evidence that alcohol’s effects also differ among the phagocytic cells (Schleifer et al, 1999). In a study of predominately male participants, phagocytosis was evaluated and investigators found that the presence of an AUD affected polymorphonuclear neutrophils (PMNs) preferentially (Parlesak et al, 2003).…”
Section: Psychoneuroimmunological Analysis Of Substance Use Disordersmentioning
confidence: 98%